1990
DOI: 10.1007/bf00589114
|View full text |Cite
|
Sign up to set email alerts
|

Cranial MRI in Wilson's disease

Abstract: Thirty-eight patients with biochemically proven Wilson's disease underwent magnetic resonance-imaging (MRI) of the brain as well as neurological examinations. The patients were scanned using spin-echo (SE) sequences; the neurologist was looking for typical symptoms: dysarthria, tremor, ataxia, rigidity/bradykinesia and chorea/dystonia. Pathological MR findings believed secondary to this uncommon inherited disorder of copper metabolism were found in twenty-two subjects. Focal abnormalities were seen in the lent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
15

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 10 publications
3
53
1
15
Order By: Relevance
“…Typical MR findings with no correlation to the clinical neurological symptoms were described in a collective of 38 patients. 22 In contrast, another MRI study of 47 patients identified three clinical subgroups. The second subgroup was associated with tremor, ataxia, and focal thalamic lesions.…”
Section: Discussionmentioning
confidence: 91%
“…Typical MR findings with no correlation to the clinical neurological symptoms were described in a collective of 38 patients. 22 In contrast, another MRI study of 47 patients identified three clinical subgroups. The second subgroup was associated with tremor, ataxia, and focal thalamic lesions.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous reports exist where focal lesions in the thalamus, the brain stem, the dentate nuclei, the cerebral white matter and the basal ganglia of patients with WD are found using magnetic resonance imaging, and their pathogenesis is extensively discussed (Aisen et al, 1985;De Haan et al, 1987;Grimm et al, 1991;Lawler et al, 1983;Magalhaes et al, 1994;Metzer and Angtuaco, 1986;Prayer et al, 1990;Roh et al, 1994). Focal edema, nerve cell loss, demyelination, gliosis, intracellular deposition of haemosiderin and cavitation have been surmised to represent the morphological changes correlating to the magnetic resonance findings in WD.…”
Section: Discussionmentioning
confidence: 95%
“…The disease is diagnosed based on clinical features, the presence of KF ring along with biochemical markers including low serum level of ceruloplasmin, increased serum copper concentration and increased urinary copper excretion (Ala et al 2007). MRI features in Wilson's disease have been well described in a number of studies (Prayer et al 1990;Starosta-Rubinstein et al 1987;Magalhaes et al 1994;Sinha et al 2006;van Wassenaer et al 1996). The disease predominantly involves deep grey matter structures, corpus callosum and brainstem.…”
Section: Introductionmentioning
confidence: 93%